(untitled) (Bangladesh Heart Journal, 2023)
Background: Heart failure is a complex syndrome that arises from abnormalities in the structure and/or function of the heart, whether inherited or acquired. It impairs the ability of the left ventricle to fill or eject blood, leading to a growing number of hospitalizations, deaths, and healthcare costs worldwide. According to the Global Burden of Disease Study 2019, heart failure affected approximately 64 million people worldwide in 2019, and caused over 3 million deaths. The prevalence of heart failure has been increasing worldwide, with an estimated 26% increase in age-standardized prevalence and a 14% increase in age-standardized incidence between 1990 and 2019. This increase in prevalence and incidence is due to a variety of factors, including the aging of the population, improved survival rates from other cardiovascular diseases, and changes in lifestyle and risk factors such as obesity and diabetes. Heart failure patients have various presentations and different etiologies. This study aimed to describe the baseline characteristics, associated co-morbid conditions, presenting features, and causes of heart failure in a study population of 3650 patients admitted to Colonel Maleque Medical College, Manikganj. Methods: This study was done to see Clinical Presentation of Heart Failure Patients admitted in Colonel Maleque Medical College, Manikganj and Maikganj Sadar Hospital. A total of 3650 patients were enrolled in this study during the period of April 2018 to March 2023. Results: Most of the patients (60%) were of 51-70 years age group. 70 % (2555) patients were male. 99% patients presented with SOB, 95% patients had basal creps, 70% had orthopnoea, 49% had Paroxysmal Nocturnal Dyspoea (PND), 40% had leg edema and 25% had raised JVP. Average heart rate was 84 beats/min, average systolic B.P. was 128 mm Hg and average diastolic B.P. was 76 mm Hg. 49% population had hypertension, 39% patients had diabetes and 28% had concomitant respiratory illness. Average EF was 37 %. Ischemic Cardiomyopathy was the commonest (40%) cause of heart failure, acute coronary syndrome was the second leading (30%) cause, valvular heart disease and hypertension are the third common causes. Conclusion: This study highlights the significant burden of heart failure in a population of patients admitted to a tertiary care hospital in Bangladesh. The findings underscore the importance of early detection and management of risk factors for heart failure, such as hypertension and diabetes, to prevent the development and progression of this condition. The identification of the most common causes of heart failure may guide targeted prevention and management strategies in this population. Most common causes are ischemic cardiomyopathy, a sequel of ischemic insult of the heart. So, patients of acute or chronic ischemic heart diseases should be treated and followed up with care, considering their socioeconomic conditions also. Bangladesh Heart Journal 2023; 38(1): 63-69